ART THERAPY DENGAN MEDIA MEWARNAI GAMBAR SEBAGAI ALTERNATIF MENINGKATKAN KEMAMPUAN REGULASI EMOSI PADA MAHASISWA BERASRAMA UNIVERSITAS MUHAMMADIYAH GORONTALO - Salahuddin Liputo; Putri Rahim; Seruni Pantulu; Mutia Hamid; Silvana Ananda; Sintiya Ladiku; Siti Khudzaifa (Elsia: Jurnal Psikologi Manusia, 2023)
This study was conducted based on the condition of poor emotional management in the dormitory of Muhammadiyah University of Gorontalo. This study aims to determine the effectiveness of art therapy techniques with coloring media as an alternative media in improving the ability to regulate emotions in boarding students at Muhammadiyah University of Gorontalo, totaling 14 women. The subject determination technique used purposive techniques. Data collection techniques used using an emotional regulation scale. The data analysis technique is descriptive statistical analysis. The results of the study showed that boarding students experienced an increase after being treated with art therapy techniques. These results are shown by descriptive data analysis, students experienced an increase in emotional regulation scores of 1.71 points after being given treatment. The average score before and after treatment was given from 29.79 to 30.50, which can be said that art therapy with coloring media can improve the ability to regulate boarding students.